Elevated Risk of Overweight/Obesity-Related Markers and Low Muscular Fitness in Children Attending Public Schools in Chile - Suarez-Reyes, M (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In Chile, children of low socioeconomic status usually attend public schools and have few opportunities to engage in healthy behaviors. This may increase their risk of overweight/obesity and low muscular fitness. Therefore, we aimed to determine the association between the school type attended with overweight/obesity-related markers and the muscular fitness of children in Chile. We included 1410 children (6–13 years old) attending public, subsidized, or private schools. Overweight/obesity-related markers included BMI Z-scores, waist circumference, and body fat percentage. Muscular fitness assessment included handgrip strength and standing long jump. The odds ratios [95% CI] of overweight/obesity, elevated waist circumference, elevated body fat, low handgrip strength, and low standing long jump were compared between school types. Compared with boys attending public schools, those attending subsidized or private schools had lower odds ratios of low handgrip strength (0.63 [0.42–0.94] and 0.44 [0.25–0.78], respectively). Girls attending subsidized schools, compared with those in public schools, had lower odds of overweight/obesity (0.63 [0.44–0.90]) and of having low handgrip strength (0.51 [0.34–0.78]). Compared with girls in public schools, those attending private schools had lower odds (vs. public schools) of overweight/obesity (0.45 [0.28–0.74]), of having elevated body fat (0.53 [0.29–0.96]), and of having low standing long jump (0.41 [0.21–0.77]). The elevated risk of overweight/obesity-related markers and lower muscular fitness in children, particularly girls, attending public schools increase their current and future disease risk. This suggests that childhood socioeconomic status plays a central role in determining disease risk. Health-promoting interventions specifically focused on children from disadvantaged contexts are required. © 2022 by the authors.